Islam and Economy: Integrating Spirituality and Welfare - Marlina Marlina; Zuhdiyah Zuhdiyah; Maryamah Maryamah; Muslih Qomarudin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Economic inequality remains a pressing issue in Indonesia, particularly between urban and rural communities. This study explores the potential of Islamic economics as an alternative system to promote justice and social welfare. Using a qualitative descriptive approach through library research, the analysis draws on scholarly literature and institutional reports to examine key principles and instruments of Islamic economics. Findings indicate that mechanisms such as zakat, infaq, and waqf contribute significantly to wealth redistribution and poverty alleviation. Despite these benefits, implementation faces challenges including low public literacy, regulatory inconsistencies, and the dominance of conventional financial practices within Islamic institutions. The study underscores the need for collaboration among government, financial institutions, and civil society to enhance education, reform policies, and innovate Islamic financial instruments. While Islamic economics offers a promising integration of spiritual and material welfare, its success depends on systemic support and stakeholder synergy. Future research should incorporate empirical field studies to validate these findings